Thinking-with-drawing: Wandering/wondering through Manning’s text - Romano, Nike (Critical Studies in Teaching and Learning, 2023)
This paper tracks different modes of thinking-with Erin Manning’s keynote address entitled ‘Radical pedagogies and metamodelings of knowledge in the making’. In so doing, the response spans the initial invitation to deliver the response, the conference presentation, the writing up of this article and the incorporation of the anonymous reviewers’ comments. The paper explores the interstices of Manning’s writing through a host of practices and processes that include reading aloud, listening, cartographic mark-making in order to make sense of and think-through the concepts that Manning addresses. The paper reveals how the ongoing iterative intra-actions generated various modes, processes, and registers – that manifest as a thinking-with-drawing – open up new ways of sense making that trouble the hegemonic affects of language